Establishing Effective Workflow Interoperability Framework In The Case Of Domino Workflow And Microsoft Exchange 2000 Server - Juliana, Wahid (2002)

(untitled)
The availability of a wide range of workflow management system (WFMS) products within the market has allowed users to adopt particular products to meet specific application needs. However, states of the art WFMSs do not have adequate features of interoperability among WFMSs. Failure of interoperability between WFMS products can cause incompatible "islands" of process automation within an organization or between organizations. The research introduces method of realizing workflow interoperability between Domino Workflow from Lotus Corporation and Microsofts Exchange 2000 Server from Microsoft Corporation. Towards the end of this research, the method used has alleviated the strategy, level and model of interoperability between different products that exist between organizations and departments. To realize the workflow interoperability, this research adopted a System Development approach that consists of five stages. The first was to construct a conceptual framework of workflow interoperability between both products. The second was to develop a system architecture. In this stage, the tools of interoperability were analysed. Only two tools were chosen, i.e. Microsoft Exchange Connector for Lotus Notes and Extensible Markup Language (XML) of Document Object Model (DOM) standard. These: tools then were modelled together with Domino Workflow and Microsoft Exchange 2000 Server in the system architecture. The third was to analyse and design the system. In this stage, a specific business process, i.e. leave application was selected to be developed as the prototype. The fourth was to build the prototype to demonstrate the practicality of the method used. Finally, the system was observed and evaluated to validate the effectiveness of the tools used. From the developed prototype, it was concluded that the use of Microsoft Exchange Connector for Lotus Notes and XML of DORA standard realized the workflow interoperability between Domino Workflow and Microsoft Exchange 2000 Server. Two models of workflow interoperability were realised from the developed prototype, i.e. Nested Sub-process model and Parallel Synchronised model. Documents (tasks) from both environments were exchanged by the XML of DOM standard that complied with the Limited Common Application Programming Interface (API) Subset level. The documents were then transferred to each other by the Microsoft Exchange Connector for Lotus Notes that corresponded with the Message Passing strategy.